أصول المبادئ التربوية الإسلامية من منظور القرآن الكريم: دراسة نظرية تطبيقية على التربية الإسلامية - Fahmi, Muhammad Azkia; Hilmi, Mamduh; Anshori, Irfan; Nurrohman, Nurrohman (Muttaqien; Indonesian Journal of Multidiciplinary Islamic Studies, 2025)
Islamic education is a conscious and directed process aimed at developing human potential comprehensively, based on the Qur’an and Hadith. Unlike general education, which focuses on the cognitive dimension, Islamic education strives to balance intellectual, spiritual, and moral aspects. This study aims to investigate the influence of appropriate educational methodology on the success of Islamic education. The method used is an in-depth literature analysis of various Islamic education sources. The results show that applying an integrated educational method, which combines classical and contextual approaches based on the values of the Qur’an and Sunnah, is effective in shaping students’ character in terms of beliefs and behavior. Furthermore, teachers who understand the basic principles of Islamic education can create a more in-depth and influential learning environment. This study recommends that the selection of appropriate methodology should be seen as a key to achieving the goals of comprehensive Islamic education, which encompasses thought, faith, and action. Thus, improvements in Islamic educational methodology are crucial for improving the quality of education and fostering character that aligns with Islamic values.